Effect of plant growth regulators on physico-chemical characters and yield of guava cv. Sardar under high density planting system - Jain, M.C.; Dashora, L.K. (Indian Journal of Horticulture, 2011)
Guava (Psidium guajava L.) belongs to family Myrtaceae and is a very common fruit, popular among rich and poors alike due to its moderate price, nourishing value and good taste. It is known as ‘apple of tropics’ and rich in vit-C and pectin content besides being a good source of other vitamins and minerals. Plant growth regulators modify or regulated physiological processes in an appreciable measure in the plant when used in a small concentration. The use of plant growth regulators has assumed an integral part of modern fruit production especially under high density orcharding to improve quality and production of fruits and use of plant growth regulators has resulted outstanding achievements in several other fruit crops with regards to improvement in quality and yield.